PENGGUNAN TEKNOLOGI DALAM PEMBELAJARAN KELAS V A DI SDIT MTA KARAWANG - Nazwa Nur Aulia Syam; Safana Hani Hamidah; Ramadhan Reza; Muhammad Dzaky (STKIP Subang, 2026)
The study was conducted over two sessions and included a control class and an experimental class. The control class did not integrate technology, whereas the experimental class utilized technology. The results of the study indicatea difference in gain scores between the pretest and posttest; the results of the pretest and posttest between the control class and the experimental class show an improvement, with the experimental class achieving a higher score than the control class.